Flebotomíneos (Diptera: Psychodidae) em um sistema agroflorestal da Região Metropolitana de Natal, Rio Grande do Norte, Brasil - Pineiro, Marcos Paulo Gomes (2010)
Sandflies stand out as important vectors of leishmaniasis. The females need to ingest blood meals, enabling them to transmit protozoa of the genus Leishmania, which may give rise to visceral leishmaniasis (VL) or American tegumentary leishmaniasis (ATL), in addition to transmitting other parasites. Leishmaniasis are important infirmities, distributed worldwide, whose infection results from the interaction of reservoir animals, the vector insect, parasitic protozoa and the healthy host. In the state of Rio Grande do Norte (RN), Brazil, these insects are important transmitters of VL, which usually presents in the most serious form. It occurs mainly in metropolitan areas, with the dog as its main reservoir and Lutzomyia longipalpis as the vector. ATL is most present in the highland areas of the state. In addition to hematophagia, engaged in by the females, both sexes need to ingest carbohydrates, which are essential to the sand flies energy requirements and may interfere in the development of Leishmania. The aim of this study was to determine the occurrence and abundance of sand flies in different environments on the farm belonging to the Empresa de Pesquisas Agropecuárias do RN (Institute of Agricultural Research of RN), in the municipality of Parnamirim, in order to relate this occurrence with climatological and biological references and eating habits. Three consecutive monthly collections were carried out with CDC traps in a fragment of the Atlantic Forest, in a residence, on a goat breeding farm and on cashew, dwarf and giant coconut, mango, banana, eucalyptus, acacia and bean plantations. A total of 1241 sandflies from eight species (Lutzomyia evandroi, Lutzomyia longipalpis, Lutzomyia shannoni, Lutzomyia sordellii Lutzomyia walkeri, Lutzomyia wellcomei, Lutzomyia whitmani, and Lutzomyia intermedia) were collected, most in the forest environment. L. longipalpis, the main VL transmitter, was confirmed as a species adapted to anthropic environments, whereas others such as L. wellcomei, the vector of ATL, occurred predominantly in forests. Carbohydrate characterization of the sand flies and plants of the region demonstrated that a number of exotic plants such as hay and eucalyptus may play some role in the adaptation of these species to modified environments. Breeding in laboratory showed a mean biological cycle of 53.5 days from egg to adulthood for L. shannoni and the possibility of diapause behavior in L. wellcomei. This study serves as a source of information that may contribute to the epidemiological vigilance of tegumentary and visceral leishmaniasis in the state, given that it analyzes the bioecology of transmitting species, as well as their potential to adapt to new environments